The Composite of 3, 4-Dihydroxyl-Phenyl Lactic Acid and Notoginsenoside R1 Attenuates Myocardial Ischemia and Reperfusion Injury Through Regulating Mitochondrial Respiratory Chain - Yan, Li; Pan, Chun-Shui; Liu, Yu-Ying; Cui, Yuan-Chen; Hu, Bai-He; Chang, Xin; Wei, Xiao-Hong; Huang, Ping; Liu, Jian; Fan, Jing-Yu; Li, Quan; Sun, Kai; et al. (Frontiers in Physiology, 2021)
Aim 3,4-Dihydroxyl-phenyl lactic acid (DLA) and notoginsenoside R1 (R1) are known to protect ischemia and reperfusion (I/R) injury by targeting Sirtuin1/NADH dehydrogenase (ubiquinone) 1 alpha subcomplex 10/the Mitochondrial Complex I (Sirt-1/NDUFA10/Complex I) and Rho-associated kinase/adenosine triphosphate (ROCK/ATP) ATP synthase δ subunit (ATP 5D), respectively. We hypothesized that a composite of the two may exhibit a more potent effect on I/R injury. The study was designed to test this hypothesis. Materials and Methods Male Sprague–Dawley rats underwent left anterior descending artery occlusion and reperfusion, with or without DLA, R1, or a combination of 3,4-dihydroxyl-phenyl lactic acid and notoginsenoside R1 (DR) pretreatment. Heart function, myocardial morphology, myocardial infarct, myocardial blood flow (MBF), apoptosis, vascular diameter, and red blood cell (RBC) velocity in venules were evaluated. Myeloperoxidase (MPO), malondialdehyde (MDA), and 8-oxo-deoxyguanosine (8-OHdG) were assessed. The content of ATP, adenosine diphosphate (ADP), and adenosine monophosphate (AMP), the activity of mitochondrial respiratory chain Complex I and its subunit NDUFA10, the Mitochondrial Complex V (Complex V) and its subunit ATP 5D, Sirt-1, Ras homolog gene family, member A (RhoA), ROCK-1, and phosphorylated myosin light chain (P-MLC) were evaluated. R1 binding to Sirt-1 was determined by surface plasmon resonance. Results DLA inhibited the expression of Sirt-1, the reduction in Complex I activity and its subunit NDUFA10 expression, the increase in MPO, MDA, and 8-OhdG, and apoptosis. R1 inhibited the increase in the expression of RhoA/ROCK-1/P-MLC, the reduction of Complex V activity and its subunit ATP 5D expression, alleviated F-actin, and myocardial fiber rupture. Both DLA and R1 reduced the myocardial infarction size, increased the velocities of RBC in venules, and improved MBF and heart function impaired by I/R. DR exhibited effects similar to what was exerted, respectively, by DLA and R1 in terms of respiratory chain complexes and related signaling and outcomes, and an even more potent effect on myocardial infarct size, RBC velocity, heart function, and MBF than DLA and R1 alone. Conclusion A combination of 3,4-dihydroxyl-phenyl lactic acid and notoginsenoside R1 revealed a more potent effect on I/R injury via the additive effect of DLA and R1, which inhibited not only apoptosis caused by low expression of Sirt-1/NDUFA10/Complex I but also myocardial fiber fracture caused by RhoA/ROCK-1 activation and decreased expression of ATP/ATP 5D/Complex V.